Marching through Georgia : my walk with Sherman - Ellis, Jerry (New York : Dell Publishing, 1996)
In today's South, Ellis found living memories of the Great Lost Cause coexisting with a modern American culture grappling with such issues as racism and social justice.
"A Delta Trade Paperback"
Reprint of Delacorte Press edition.
Keywords: Ellis, Jerry -- Journeys -- Georgia; Sherman's March to the Sea; Georgia -- Description and travel